Analysis of grain density and yield characters in aromatic rice genotypes. - Shahid, M. Shahidullah; Musa, Mohamed Hanafi; M. Ashrafuzzaman,; Uddin, Md. Kamal; Ismail, Mohd Razi (Colegio de Postgraduados, 2010)
Aromatic rices (Oryza sativa L.) normally produce enormous spikelets of low grain weight resulting low yield. Grain weight and grain density are the vital indicators of grain filling and mainly dependent on genetic make-up. Detail study of grain density and yield components of aromatic rice is a crucial need for yield improvement. An experiment was conducted with 40 rice genotypes to assess the grain density of aromatic rices and to observe the relationships of different grain categories with yield characters. The percentage of high density grains, good grains, average grains, poor grains, partially filled grains, spikelet sterility, and thousand grain weight were found to vary in a great extent. Maximum 50 % high density grain was harvested in BR39 and a minimum 1 % in Khazar. Thousand grain weight ranged from 10 g to 30 g. The proportion of high density grains was positively correlated with thousand grain weight (r=0.57) and grain yield (r=0.57). The negative relations were found between spikelet sterility and grain yield (r=0.47) and also between number of grains and thousand grain weight (r=0.74). The grain yield showed the highest positive direct relation (0.23) with thousand grain weight, followed by high density grains (0.20).